KOMUNIKASI PENDIDIKAN ANAK DI TENGAH PANDEMI : HOMESCHOOLING SEBAGAI ALTERNATIF PILIHAN ORANG TUA SETELAH SEKOLAH FORMAL - Mira Hasti Hasmira (Jurusan Ilmu Komunikasi Universitas Andalas, 2021)
The Covid 19 pandemic has devastated the education system in Indonesia. Children who should enjoy education in formal schools using face-to-face methods, change to distance learning. This raises new problems. To overcome this, it is very necessary to communicate proper education so that children's education can continue as it should. One of the alternative choices for children's education by parents due to the pandemic is homeschooling. homeschooling enthusiasts are soaring amid this pandemic. This paper examines the educational communication that occurred in the implementation of homeschooling in the midst of the Covid 19 pandemic. This paper is in the form of descriptive qualitative data collection methods through participatory observation, interviews and documentation study. The findings in this paper are analyzed using Bruner's learning theory, which focuses on how a person influences others so that the learning process occurs within him. Analysis was also carried out with William Schutz's Fundamental Interpersonal Relationship Orientation (FIRO). This theory emphasizes three kinds of human needs, namely the need for inclusion, the need for control and the need for affection. The result of this research is that educational communication occurs effectively considering that between communicators, namely parents as teachers and children as students and communicants know each other very well, so that parents as teachers can choose and use appropriate teaching methods according to the character of their children. and able to reduce distraction. Teaching materials are also tailored to the needs of children. Besides the national curriculum, parents can also add material that is in accordance with the character of the child.